Metaheuristic Algorithm for university timetabling problem - Wahid, Juliana; Abdul Rahman, Syariza; Mohamed Din, Aniza (Universiti Utara Malaysia, 2021)
The current implementation of the Academic Affairs Department of Universiti Utara Malaysia (HEA, UUM) in scheduling the course timetabling is by using a ready-made software package system in which the timetable is created manually. This is a long process since all necessary data need to be entered into the system. With huge number of curriculum and students, the introduction of base curriculum model and the use of metaheuristic algorithm would ease the curriculum-based timetabling process. This study started by modelling the base curriculum and data set of UUMCOLGIS. The hybridization of HSA and GD metaheuristic approaches were implemented and executed on the data set. The approach produce better result in terms of lower total penalties of soft constraints compared to the result of spreadsheet timetable obtained from HEA, UUM. This study can ease the HEA in scheduling the course timetabling that dynamically increase in number of curriculum and students in the future.